2014
DOI: 10.1093/cvr/cvu113
|View full text |Cite
|
Sign up to set email alerts
|

Quantitative proteomics analysis reveals similar release profiles following specific PAR-1 or PAR-4 stimulation of platelets

Abstract: Both ELISA on established α-granule proteins and MS-based quantitative proteomics showed that the most abundant α-granule proteins are released in similar quantities from platelets after stimulation with either PAR-1 or PAR-4. Our findings provide evidence against the hypothesis that PAR-1 and PAR-4 stimulation of platelets trigger differential release of alpha-granule, but further studies are needed to draw conclusions for physiological conditions.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

3
56
1
4

Year Published

2015
2015
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 69 publications
(65 citation statements)
references
References 12 publications
3
56
1
4
Order By: Relevance
“…Selective packaging of proteins within different subpopulations of a-granules in platelets has been a matter of controversy. 40,41 For example, vascular endothelial growth factor, a proangiogenic protein, was shown to be stored in a different a-granule population than endostatin, an antiangiogenic protein. 34 Conversely, it has been proposed that random distribution of proteins into a-granules occurs.…”
Section: Discussionmentioning
confidence: 99%
“…Selective packaging of proteins within different subpopulations of a-granules in platelets has been a matter of controversy. 40,41 For example, vascular endothelial growth factor, a proangiogenic protein, was shown to be stored in a different a-granule population than endostatin, an antiangiogenic protein. 34 Conversely, it has been proposed that random distribution of proteins into a-granules occurs.…”
Section: Discussionmentioning
confidence: 99%
“…30 A study of thrombin-induced release showed .90 proteins in platelet releasate. 31 In addition, the platelet protein content highly fluctuates in donors depending on gender, age and physiological state. 30 In a recent study, Mussano et al 32 performed a similar X-MAP multiplex assay on male and female platelets.…”
mentioning
confidence: 99%
“…Avanços importantes podem ser vistos em diversos trabalhos sobre a composição das proteínas plaquetárias humanas, analisando plaquetas em repouso e ativadas (Marcus et al, 2000;O'Neill et al, 2002;García et al, 2004a;Martens et al, 2005;Qureshi et al, 2009;Májek et al, 2010;Burkhart et al, 2012), proteínas pertencentes à membrana plasmática (Moebius et al, 2005;Maguire et al, 2005;Senis et al, 2007;Tucker et al, 2009), proteínas secretadas após ativação com diferentes agonistas (McRemond et al, 2004;Coppinger et al, 2004Coppinger et al, e 2007Piersma et al, 2009;Wijten et al, 2013;van Holten et al, 2014;Vélez et al, 2015), proteínas presentes em micropartículas plaquetárias (García et al, 2005;Capriotti et al, 2013;Aatonen et al, 2014;Milioli et al, 2015) e nos grânulos alfa e densos Embora exista uma extensa literatura sobre função plaquetária, ainda pouco se sabe sobre os mecanismos que regem a secreção, tanto de proteínas como de pequenas moléculas, e também, de vesículas extracelulares (micropartículas e exossomos) durante processos fisiológicos e patológicos. O conhecimento mais acurado sobre o proteoma e o secretoma de plaquetas, em diferentes condições de ativação, poderá contribuir para o entendimento dos mecanismos que regem este sistema e também, no desenvolvimento de novos alvos para terapias antiplaquetárias.…”
Section: Análise Proteômica De Plaquetasunclassified
“…A maioria dessas proteínas já foi descrita por outros autores que analisaram o secretoma de plaquetas Wijten et al, 2013;van Holten et al, 2014;Vélez et al, 2015), e também serão descritas adiante em nossa análise do sobrenadante de plaquetas ativadas.…”
Section: Sedimento De Plaquetasunclassified
See 1 more Smart Citation